Gender, sex, family, and revolution Women in the Huk rebellion in the Philippines, 1942-1956 - Lanzona, Vina Albero (Bell & Howell Information and Learning Company, 2001)
In the long history of Philippine agrarian unrest, the Huk rebellion (1942--1956) is considered the most important of the country's peasant revolutions. Drawing on interviews with over a hundred guerrilla veterans in Manila and Central Luzon, as well as documentary research, my dissertation presents the Huk rebellion from within, focusing on the role of women, gender, family and sexuality. I argue that these issues--usually treated as personal matters peripheral to the revolution--shaped the internal dynamics of the Huk movement. When for the first time in Philippine history a significant number of women were mobilized in this struggle, the Huk movement was confronted with the challenge of balancing society's normative sexual culture and the Communist Party's own revolutionary gender relations. Mobilized through complex social networks, the identities Huk women were transformed from daughters, sisters and wives of Huk men to their comrades and fellow revolutionaries. Despite these new identities, most women guerrillas reproduced traditional societal roles inside the revolution, performing tasks such as cooking, washing, and housekeeping. While most women remained subordinate to men and were relegated to subsidiary roles, some threatened social conventions by becoming Politburo leaders and combat commanders. The exceptional number of women commanders, the so-called Huk Amazons, represents a radical departure from society's dominant culture. These women not only threatened the social order, but also the gender order where women are the muses, and men the warriors. A number of women became the mistresses of Huk men, prompting the Party leadership to devise a revolutionary solution to the "sex problem," undoubtedly one of the movement's major dilemmas. This so-called solution allowed men to take advantage of women and clearly did not empower the female cadres. Despite its egalitarian ideology, the male-dominated Huk movement was undercut by its patriarchal assumptions about appropriate gender roles and sexuality. The movement diminished the potential contribution of women and failed to address the needs and deep-seated aspirations of all its followers, both male and female. In the end, the Huk revolt failed not only because of successful government counterinsurgency operations, but also because of these internal flaws.--Abstract.